2020
DOI: 10.1021/acsami.0c01449
|View full text |Cite
|
Sign up to set email alerts
|

Printing a Wide Gamut of Saturated Structural Colors Using Binary Mixtures, With Applications in Anticounterfeiting

Abstract: Use of colloidal suspensions to generate structural colors has the potential to reduce the use of toxic metals or organic pigments in inkjet printing, coatings, cosmetics, and other applications, and is a promising avenue to create large-scale nanostructures that produce long-lasting colors. However, expanded use of structural colors requires a reduction in coffee-ring effects during printing, which currently requires intricately patterned substrates or high particle concentrations, and diversification of colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…[ 57 ] Researchers have used this strategy of mixing absorbing and nonabsorbing components to tune structural colors in the past. [ 39,58 ] However, whether the extent of mixing between the absorbing and nonabsorbing species affects structural coloration, as has been observed in case of some avian species, has not been systematically studied yet.…”
Section: Resultsmentioning
confidence: 99%
“…[ 57 ] Researchers have used this strategy of mixing absorbing and nonabsorbing components to tune structural colors in the past. [ 39,58 ] However, whether the extent of mixing between the absorbing and nonabsorbing species affects structural coloration, as has been observed in case of some avian species, has not been systematically studied yet.…”
Section: Resultsmentioning
confidence: 99%
“…18 In particular, two unique optical properties of melanin have been of interest for decades. One is the high refractive index (RI, $1.7-1.8), which results in vibrant structural colors 11,[19][20][21][22][23][24][25][26][27] and applications for medical diagnostics. [28][29][30] The second is the broadband absorption, which is responsible for enhancing saturation in structural colors, 11,[19][20][21][22][23][24][25][26][27] protection against UV radiation, 31,32 thermoregulation and imaging, [33][34][35] and optical contrast in photoacoustic imaging.…”
mentioning
confidence: 99%
“…One is the high refractive index (RI, $1.7-1.8), which results in vibrant structural colors 11,[19][20][21][22][23][24][25][26][27] and applications for medical diagnostics. [28][29][30] The second is the broadband absorption, which is responsible for enhancing saturation in structural colors, 11,[19][20][21][22][23][24][25][26][27] protection against UV radiation, 31,32 thermoregulation and imaging, [33][34][35] and optical contrast in photoacoustic imaging. 36 Both of the above properties are expected to be influenced by UV radiation, especially considering melanin's tendency to undergo structural changes when it acts as a UV-protective agent with UV-dissipative and radical-scavenging abilities.…”
mentioning
confidence: 99%
“…of SiO 2 and PDA particles on an epoxy resin film containing thermochromic microcapsules that change from white to black with temperature ( Figure 9c) [116]. Additionally, it was shown that colloidal assemblies were efficiently constructed with a small amount of colloidal dispersion by using a substrate whose surface was perfluorinated by the cold plasma method.…”
Section: Anti-counterfeiting Applicationmentioning
confidence: 96%